Transcendent and Immanentperception and Cognitive Equilibrium in Space-Time (London Journal of Research In Humanities and Social Sciences, 2024)
Perception is generated through the sensation captured by the sensors in a transcendental way, as well as through apperception in animmanent way as a result of memories; Bothsenses are valued in sensitivity and generate the first cognitive perceptual image. In everyday life, as well as in scientific and technological life, perceptions-emotions are based on actsacquired by teaching and learning, both; family, educational, social coexistencesuch as laws, rites, percepts and norms. Hencetheexpressions in reality that are embodied in matter in time and spaceon the basis of perceptions – emotions called “precepts” that express the modes of social being of human groups in certain sociocultural conditions. The seexpressions will be interpreted a posteriori by apperceptions that are the product of cognitive, perceptive, emotional and volitionalsyn theses, which are kept in the “cognitive balance”. From where, what is expressed and represented in reality is understood by what iskept in the cognitive balance, which can be accepted orrejected, but, if there is acceptance, a significant transcendental and immanent fulfill mentisobtained, which can lead in its maximum expression to a mental rapture, both; scientific, aesthetic, mystical, as well as spiritual.
Keywords: trascendentperception; immanentperception; cognitive equilibrium